International sexual partnerships may be shaped by sexual histories and socioeconomic status - Hong Ha M. Truong (2018)
Exchange sex and higher education were associated with an increased likelihood of international sexual partnerships (ISPs). Exchange sex and older age were associated with an increased likelihood of condomless sex in ISPs. Educational and socioeconomic factors may create unbalanced power dynamics that influence exchange sex and condomless sex in ISPs.